2017
DOI: 10.3389/fmicb.2017.00335
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Genomic Feature of a Virulent Klebsiella pneumoniae Sequence Type 14 Strain of Serotype K2 Harboring blaNDM–5 in China

Abstract: The objective of this study was to reveal the molecular mechanism involved in carbapenem resistance and virulence of a K2 Klebsiella pneumoniae clinical isolate 24835. The virulence of the strain was determined by in vitro and in vivo methods. The de novo whole-genome sequencing technology and molecular biology methods were used to analyze the genomic features associated with the carbapenem resistance and virulence of K. pneumoniae 24835. Strain 24835 was highly resistant to carbapenems and belonged to ST14, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Fortunately, no hypervirulence genes were found albeit capsule type K2, identified in some strains ( Figs. 9-12), are associated with increased virulence and resistance [67][68][69] . It is interesting to note that the K2 serotype was also identified in a ST14 strain (K118) in this study as was reported in China recently 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, no hypervirulence genes were found albeit capsule type K2, identified in some strains ( Figs. 9-12), are associated with increased virulence and resistance [67][68][69] . It is interesting to note that the K2 serotype was also identified in a ST14 strain (K118) in this study as was reported in China recently 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Gu and colleagues [13] have reported acquisition of a hvKp virulence plasmid by a carbapenem-resistant cKp strain, which caused an outbreak of 5 cases in a Chinese hospital ICU, and uniformly fatal outcomes in the patients affected. A strain of hvKp possessing bla NDM-5 has also been described [14]. In light of these data, it is probable that further convergence of multidrug resistance genes with hypervirulent K. pneumoniae will occur.…”
Section: The Increasing Prevalence Of Mdr and Xdr Hvkp Is Problematicmentioning
confidence: 95%
“…Once the bla KPC-2 gene is introduces into a certain location, especially in a hospital setup, under antibiotic selection pressure, further dissemination of this gene may occur which may lead to MDR and XDR strains. Hypermucoviscous K. pneumoniae (HMKP) strain types which are sporadically distributed in Asia and the Middle East are the NDM-producing isolates [12,13]. Liu et al [14], had reported the first outbreak of CR-HMKP strains which harbored bla NDM-1 gene, shared the same pulsotypes (PT) and belong to the same Sequence types (ST).…”
Section: Klebsiella Pneumoniae: the Classical And Other Subtypesmentioning
confidence: 99%